2004
DOI: 10.1002/bem.10199
|View full text |Cite
|
Sign up to set email alerts
|

High frequency electromagnetic fields (GSM signals) affect gene expression levels in tumor suppressor p53‐deficient embryonic stem cells

Abstract: Effects of electromagnetic fields (EMF) simulating exposure to the Global System for Mobile Communications (GSM) signals were studied using pluripotent embryonic stem (ES) cells in vitro. Wild-type ES cells and ES cells deficient for the tumor suppressor p53 were exposed to pulse modulated EMF at 1.71 GHz, lower end of the uplink band of GSM 1800, under standardized and controlled conditions, and transcripts of regulatory genes were analyzed during in vitro differentiation. Two dominant GSM modulation schemes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 41 publications
4
64
1
1
Order By: Relevance
“…EMF is a recent addition to the list of physical stimuli. It was initially shown in the power frequency (extremely low frequency, ELF) range [13], but shortly afterwards, radio frequency (RF) fields [15] and amplitude modulated RF fields [16] were shown to activate the same stress response.…”
Section: Physiological Stress and Cellular Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…EMF is a recent addition to the list of physical stimuli. It was initially shown in the power frequency (extremely low frequency, ELF) range [13], but shortly afterwards, radio frequency (RF) fields [15] and amplitude modulated RF fields [16] were shown to activate the same stress response.…”
Section: Physiological Stress and Cellular Stressmentioning
confidence: 99%
“…This may also be true of cancer cells, although some (e.g., MCF7 breast cancer cells) have responded to EMF [38,39], and in HL60 cells, one cell line responds to EMF while another does not [24]. Czyz et al [16] found that p53-deficient embryonic stem cells showed an increased EMF response, but the wild type did not.…”
Section: Cells Affected By the Stress Responsementioning
confidence: 99%
“…However, these changes are not seen in several other cell types . RF fields have also been reported to up-regulate expression of HSP70 protein in a p53-deficient mouse embryonic stem cell line [Czyz et al, 2004], though this effect was not seen in the presence of functional p53. These findings are supported by several gene-array studies showing significant shifts in the expression of a small subset of genes following RF irradiation [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly the interest of researchers is concentrated on genes coding the proteins connected with the process of regulation of gene activity, for instance, the proteins c-jun, c-myc; or proteins connected with stress reaction of cells, first of all so-called heat shock proteins, for instance, hsp-70; or very important regulatory proteins p53 and p21. There are evidences of microwave exposure (1,71 GHz) influence on hsp70, c-jun, c-myc, and p21 levels in p53-deficient cells, but not in wild-type cells [79]. The EMF-induced changes of the transcript level of cell cycle regulatory and apoptosis-related genes were shown [80,81].…”
Section: The Action Of Emf On Intracellular Regulatory Systemsmentioning
confidence: 96%